Harvesting: From Manual to Mechanical - Stephen H. Futch; J. D. Whitney; Jacqueline K. Burns; Fritz M. Roka (EDIS)
Mechanical harvesting and many other improvements in harvesting of Florida citrus have their origins in the mid-1950s. During the 1950s and 1960s, a consistent labor supply for hand harvesting was becoming increasingly difficult to obtain and acreage along with yields of Florida citrus was steadily increasing. These concerns led to the development of a citrus mechanical harvesting program spearheaded by the Florida Department of Citrus, United States Department of Agriculture and the University of Florida. The program sought to develop harvesting systems to remove or aid in the removal of fruit from the trees, thereby reducing the number of hand harvestors needed. Industry interest in mechanical harvesting decreased in the 1980s when the devastating freezes of 1983, 1985 and 1989 decreased acreage and volume of fruit to be harvested. This document is HS-1017, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date May 2005.